2011
DOI: 10.1073/pnas.1101881108
|View full text |Cite
|
Sign up to set email alerts
|

Expression of chemokine receptor CXCR3 on T cells affects the balance between effector and memory CD8 T-cell generation

Abstract: Generation of a robust immunological memory response is essential for protection on subsequent encounters with the same pathogen. The magnitude and quality of the memory CD8 T-cell population are shaped and influenced by the strength and duration of the initial antigenic stimulus as well as by inflammatory cytokines. Although chemokine receptors have been established to play a role in recruitment of effector CD8 T cells to sites of inflammation, their contribution to determination of T-cell fate and shaping of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
152
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(163 citation statements)
references
References 52 publications
(65 reference statements)
10
152
1
Order By: Relevance
“…This redistribution was impaired when the CD8 + T cells lacked expression of CXCR3. It was suggested that this redistribution within the priming organ and the consequent longer or shorter contact with Ag-presenting DCs determined the long-term fate of the CD8 + T cells (51,52). Our data are in full agreement with the concept that CXCR3 and CXCL10 play a role in the localization of primed CD8 + T cells at the site of priming and, thereby, affect the CD8 + T cell response.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This redistribution was impaired when the CD8 + T cells lacked expression of CXCR3. It was suggested that this redistribution within the priming organ and the consequent longer or shorter contact with Ag-presenting DCs determined the long-term fate of the CD8 + T cells (51,52). Our data are in full agreement with the concept that CXCR3 and CXCL10 play a role in the localization of primed CD8 + T cells at the site of priming and, thereby, affect the CD8 + T cell response.…”
Section: Discussionsupporting
confidence: 81%
“…We now add that CXCL10 performs such a function for CD8 + T cells, in accordance with a recent finding that CXCL10 produced by DCs can support the generation of a CD8 + T cell response (50). Interestingly, recent findings on the role of CXCR3 in fate determination of primed CD8 + T cells further support this notion (51,52). CXCR3 binds CXCL9, CXCL10, and CXCL11, but C57BL/6 mice only express CXCL9 and CXCL10 (52).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…CD27-CD70 interactions have been shown to induce autocrine IL-2 production in CD8 ϩ T cells, thereby promoting their survival (18). Activated T cells may also express CXCR3, a chemokine receptor required for T cell chemotaxis to the site of antigen (19,20). Moreover, individual expression of IL-7R, CD27, and CXCR3 has been used to identify memory CD8 ϩ T cell populations with an efficient recall response (21).…”
mentioning
confidence: 99%